A preparation method and equipment for manufacturing nano high-aluminum material using secondary aluminum ash fire method
The method of preparing nano high-aluminum materials by secondary aluminum ash fire method is to remove harmful substances in secondary aluminum ash through primary pre-firing and secondary calcining steps, and the problem of insufficient performance of refractory materials in the prior art is solved, achieving high Preparation of nano-high aluminum materials and effective utilization of aluminum ash resources.
Patent Information
- Application Number
- CN202411431186.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-14
AI Technical Summary
In the prior art, when using secondary aluminum ash to prepare refractory materials, heavy metals and halogenated salts are not effectively removed, resulting in insufficient product performance, insufficient refractory resistance and heavy metal pollution problems.
The preparation method for manufacturing nano high-aluminum materials by secondary aluminum ash fire method is used to remove or convert harmful substances in aluminum ash through primary pre-firing and secondary calcining steps to enhance the performance of nano high-aluminum materials. The specific steps include dry grinding and refining the raw materials, absorption of oxygen calcining after sphere formation, adding nanometal oxides and dispersants to the secondary ingredients, and achieving high-temperature solid phase reaction by adjusting pH and dehydration treatment to form high-performance nanoalumina.
Effectively remove harmful substances in aluminum ash, improve the wear resistance and high temperature resistance of nano high-aluminum materials, enhance product performance, is suitable for large-scale production, and achieve efficient utilization of aluminum ash resources.
Smart Images

Figure CN118955115B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of refractory materials, and in particular to a preparation method and equipment for manufacturing nano high-aluminum materials by utilizing a secondary aluminum ash fire method. Background Art
[0002] Secondary aluminum ash, also known as black ash, is mainly the waste after the extraction of metallic aluminum from primary aluminum ash or the aluminum-containing waste slag produced in the aluminum refining process. Secondary aluminum ash is a hazardous waste that contains a large amount of toxic and harmful substances such as fluoride, cyanide, aluminum carbide, and aluminum amide. The pyrometallurgical treatment of secondary aluminum ash mainly relies on the calcination process under high temperature conditions. In this way, the valuable components in the secondary aluminum ash can be recycled and harmlessly treated. The advantage of pyrometallurgical treatment is that it can effectively treat secondary aluminum ash under high temperature conditions, which is suitable for projects with large processing volume and large investment scale.
[0003] CN105294135A proposes a method for directly preparing aluminum spinel refractory materials using aluminum ash and the materials prepared therefrom. The technical scheme is as follows: 50-90wt% of aluminum ash is mixed with 10-50wt% of magnesium-containing or zinc-containing raw materials, and 0.1-0.5wt% of sintering aid is added to the mixture, and the mixture is ball-milled and mixed to form the mixture, and the formed body is heated to 1000-1400℃ at a heating rate of 2-10℃ / min in a high-temperature reaction furnace, and kept warm for 1-5h, and then cooled to room temperature to obtain aluminum spinel refractory materials. Aluminum ash solid waste is used as raw material, and the raw material has a wide range of applications, which better solves the problem of comprehensive utilization of aluminum ash and its secondary pollution to the environment. However, the components in aluminum ash are complex, and the direct use of aluminum ash will cause insufficient product performance, such as insufficient refractoriness, and expansion of heavy metal pollution. CN115947611B relates to a method for preparing refractory materials from secondary aluminum ash. The preparation method provided by the invention classifies the direction of resource application of secondary aluminum ash. When the mass percentage of silicon dioxide in the secondary aluminum ash is less than 5%, it can be used to prepare alkaline alkaline magnesium-aluminum refractory materials; when the mass content of silicon dioxide in the secondary aluminum ash is ≥5%, it can be used to prepare acidic acidic magnesium-aluminum-silica refractory materials. The invention classifies the secondary aluminum ash and obtains refractory materials through one-step sintering. The method provided by the invention classifies the secondary aluminum ash, and while reducing the cost of secondary aluminum ash treatment, it adopts one-step sintering, and at the same time realizes the low-cost harmless disposal and resource utilization of secondary aluminum ash, simplifies the processing steps of secondary aluminum ash, realizes energy conservation and emission reduction, and the prepared refractory materials have the characteristics of high density and can be widely used in the field of refractory materials. However, it does not exclude the heavy metals and halide salts therein, which will still cause insufficient product performance, such as insufficient refractoriness, expansion of heavy metal pollution and other problems. Summary of the invention
[0004] In order to solve the above problems, the present invention proposes a preparation method and equipment for manufacturing nano high-aluminum materials using secondary aluminum ash pyrolysis. Through secondary sintering, harmful substances in the aluminum ash are removed or converted into a strengthening phase, which can enhance the performance of the nano high-aluminum material. The process is simple, suitable for large-scale production, and is conducive to the resource utilization of aluminum ash.
[0005] To achieve the above object, the technical solution of the present invention is:
[0006] A method for preparing nano high-aluminum material by secondary aluminum ash pyrolysis method comprises the following steps:
[0007] Step (1) primary batching: taking 10 parts by weight of aluminum ash passed through a 100-mesh sieve, adding 1-2 parts of graphite, 0.1-0.2 parts of boric acid, 0.5-1 parts of calcium carbonate and 0.1-1 parts of sodium silicate, dry-grinding to an average particle size of 0.8-1.0 μm to obtain a mixed material, and pelletizing the mixed material to obtain a ball material;
[0008] Step (2) primary pre-calcination: the ball material is sent to 800-1000°C and calcined in anoxic conditions for 2-4 hours to obtain a primary pre-calcined material;
[0009] Step (3) secondary batching: taking 10 parts of the primary pre-sintered material by weight, crushing it and passing it through a 100-mesh sieve, adding 4-6 parts of nano metal oxide particles, 3-5 parts of aluminum sulfate, 3-4 parts of sodium aluminate and 0.01-0.03 parts of a dispersant, mixing and adding to 30-50 parts of water, adjusting the pH to 6-8 with a pH regulator, ball milling to an average particle size of 0.8-1.0 μm, unloading, dehydrating and molding to obtain a green body;
[0010] Step (4) Calcination: The green body is sent to a calcination device for calcination, and after cooling, a nano high-aluminum material is obtained.
[0011] This scheme realizes the preparation of nano high-aluminum materials through secondary calcination. In the first pre-calcination, the main functions of the dry grinding process in this scheme are: 1. to refine the particle size of the raw materials, increase the reaction contact surface, and improve the reaction activity; 2. to densify the raw materials and increase the reaction probability; 3. to mix the materials evenly. The ball-making process of this scheme requires the addition of water as a binder, in which part of the boric acid will dissolve in the ball-making water and then penetrate into the ball material. In step (2), the first pre-calcination material is achieved by anaerobic calcination. During the calcination process, graphite will react with aluminum nitride to generate aluminum carbide and nitrogen, and boric acid will decompose into boron atoms and react with aluminum nitride to generate nitrogen boron aluminum. The role of calcium carbonate is: 1. decompose to produce carbon dioxide and take away nitrogen; 2. promote the decomposition of sodium silicate, and react with sodium silicate and fluoride to generate calcium fluorosilicate, and transform into soluble fluoride. The average particle size needs to be 0.8-1.0μm. If the particle size is too coarse, the reaction is incomplete; if the particle size is too fine, it is difficult to make balls. The first pre-firing removes aluminum nitride and converts part of the fluoride into soluble salt calcium fluosilicate, which can effectively remove fluoride. The introduction of high-strength ceramic materials such as aluminum carbide and nitrogen-boron aluminum can become non-uniform nucleation points during the secondary calcination process, hindering the expansion of cracks and enhancing the wear resistance and high temperature resistance of the product.
[0012] In the secondary ingredients, aluminum sulfate and sodium aluminate react to form aluminum hydroxide, which is dispersed during the ball milling process. The roles of aluminum hydroxide are: 1. As an active substance, it generates nano-alumina during high-temperature calcination, making the high-temperature solid-phase reaction more active; 2. As a flocculant, it is beneficial to dehydration. The role of the dispersant is to enable the nano-metal oxide to be dispersed in the system, which is beneficial to the uniformity of the high-temperature solid-phase reaction during the calcination process. During the ball milling process, as the powder is broken and refined, soluble fluorides and chlorides will enter the water and be discharged with the dehydration process. The secondary ball milling is ball milled to an average particle size of 0.8-1.0μm, which takes into account the activity of the solid-phase reaction.
[0013] Preferably, in step (1), the mixing ball-forming process is as follows: continuously and evenly adding the mixing material into a disc ball-forming machine, the mixing material moves with the disc ball-forming machine, and during the process a sucrose solution with a concentration of 1%-5% is sprayed on the mixing material until the mixing material is rolled into balls with a diameter of 0.8-1.5 cm.
[0014] The average particle size of the material is fine, and the strength of the ball material is low when it is directly made into balls, that is, the density of the ball material is insufficient, resulting in insufficient reaction. In order to improve the strength of the ball material, this scheme uses sucrose solution as a binder. At the same time, sucrose can be calcined in anoxic conditions during the first pre-burning to generate nano-carbon particles, which can assist in the decomposition of aluminum nitride. The diameter of the ball material should not be too large, as it is easy to cause a large temperature difference between the surface and the core of the ball material, and the reaction gas is not easy to overflow.
[0015] Preferably, in step (2), the anaerobic calcination is calcination under a nitrogen atmosphere.
[0016] Preferably, in step (2), the heating process of the anaerobic calcination is: from room temperature to 300°C, the heating rate is 1-3°C / min; from 300°C to final temperature, the heating rate is 3-5°C / min.
[0017] The process from room temperature to 300°C is mainly a drying process. In order to reduce the segregation of boric acid, the heating rate should not be too fast.
[0018] Preferably, in step (3), the nano metal oxide particles are one or more of nano magnesium oxide, nano zinc oxide, nano manganese oxide, and nano iron oxide.
[0019] In specific operations, the performance of the final product can be adjusted by adding different proportions of nano-metal oxide particles.
[0020] Preferably, in step (3), the pH adjuster is citric acid and sodium citrate; and the dispersant is sorbitol or calcium gluconate.
[0021] In step (2), pH adjustment is to make the hydrolysis reaction more complete. Although the particle size of the material system after ball milling is small, there is a large amount of Al(OH)3 in the system, which acts as a flocculant, causing the material to agglomerate and facilitate dehydration.
[0022] Preferably, in step (3), the dehydration method is centrifugal dehydration, and the water content of the green body is 5-8%.
[0023] If the moisture content of the green body is too low, cracks will appear on the surface of the green body perpendicular to the direction of the molding pressure; if the moisture content is too high, the energy consumption will be high, and it will be difficult to control the size of the finished product, affecting the consistency of the product.
[0024] Preferably, in step (4), the calcination process is: heating from room temperature to 300°C at a rate of 3-5°C / min, heating from 300°C to 1000°C at a rate of 5-8°C / min, heating from 1000°C to final temperature at a rate of 8-15°C / min, and keeping warm for 10-30 minutes; the final temperature is 1250-1550°C.
[0025] Preferably, in step (4), the cooling rate is 0.5-5°C / s.
[0026] Too fast cooling rate, especially just after calcination, will lead to dark cracks, or even direct cracking and scrapping. Dark cracks may be caused by the large difference in contraction between the glass phase on the grain and the grain boundary caused by too fast cooling rate.
[0027] The temperature is increased at a rate of 3-5°C / min from room temperature to 300°C in order to fully discharge the residual moisture in the green body and prevent cracking caused by moisture; most hydroxides and carbonates are decomposed in the 300-1000°C temperature range, and the temperature is increased at a rate of 5-8°C / min to ensure uniform overflow of gas or moisture and obtain a good micropore distribution effect; the temperature is increased at a rate of 8-15°C / min from 1000°C to the final temperature in order to rapidly nucleate and increase the number of nuclei. At the same time, the holding time should not be too long to prevent excessive growth of grains or excessive enlargement of micropores beyond the nanoscale.
[0028] The present scheme also discloses an equipment for manufacturing nano-high-aluminum materials by the above-mentioned secondary aluminum ash fire method, which includes, in order of material flow: a first batching barrel, a first ball mill, a disc ball making machine, an atmosphere furnace, a second ball mill, a second batching barrel, a third ball mill, a dehydrator, a molding device, a calcining device, and a cooling device.
[0029] The material flow process in the equipment of the secondary aluminum ash pyrometallurgical manufacturing scheme for preparing nano-high aluminum materials described in this scheme is as follows: aluminum ash and auxiliary materials are weighed according to the ratio and enter the first batching barrel, and enter the first ball mill after the weighing is completed. After the ball milling and mixing to the target particle size, the ball material is balled in the disc ball making machine to obtain the ball material, and the ball material enters the atmosphere furnace for the first pre-burning, and after the first pre-burning and cooling, it enters the second ball mill for crushing and fine grinding to the target particle size, and then the second batching is carried out in the second batching barrel. After the batching is completed, it enters the third ball mill for ball grinding to the target particle size and dehydration, and then enters the molding equipment, and enters the calcining equipment after molding. After the calcination is completed, it enters the cooling equipment, and the finished product is obtained after cooling. The material flow between the above-mentioned parts, that is, the connection between the various equipment is realized through conventional pipelines, augers or conveying equipment.
[0030] Preferably, the atmosphere furnace includes a rotating bearing, a rolling cylindrical kiln body mounted on the rotating bearing, the two ends of the kiln body are respectively connected to a feed end cover and a discharge end cover through a rotating bearing, the feed end cover is provided with a feed port, and the discharge end cover is provided with a discharge port and an air inlet; the kiln body is divided into a drying section and a reaction section in sequence according to the feeding and discharging direction, the reaction section is provided with a reaction section shell, and a heating component is provided on the inner side of the reaction section shell.
[0031] The reaction section is provided with a reaction section shell, which serves to support the heating components and also to keep the heat in. The anaerobic environment described in this scheme refers to the absence of oxygen in the kiln body, which is mainly achieved by sealing the cover, while nitrogen is introduced through the air inlet to ensure that the reaction section is an anaerobic environment.
[0032] Compared with the existing technology, the advantages of this solution are:
[0033] In terms of technology: aluminum nitride and fluoride are removed through formula control, primary pre-firing parameter control, ball milling and other process combinations. At the same time, high-performance ceramic particles such as aluminum carbide and nitrogen-boron-aluminum are introduced as non-uniform nucleation points during secondary calcination, which can hinder the expansion of cracks in the finished product and improve the performance of the secondary sintered product. On the basis of primary pre-firing, the secondary calcination controls the secondary additives, the particle size of the powder before calcination, the moisture content of the green body, and the control of the calcination process, so as to achieve the production of high-performance nano-high-aluminum materials.
[0034] Equipment: Through the transformation of the atmosphere furnace, the primary pre-firing can be realized in an oxygen-free environment. In this solution, the feed end cover and the discharge end cover are connected by rotating bearings at both ends of the kiln body. The gas outlet is only at the feed port and the discharge port, so the oxygen environment is not good. At the same time, inert gases such as nitrogen are introduced into the air inlet to further ensure the oxygen environment. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 It is the overall diagram of the equipment of the present invention.
[0037] Figure 2 It is a cross-sectional structural diagram of the atmosphere furnace of the present invention.
[0038] In the figure: 1 first batching barrel, 2 first ball mill, 3 disc ball making machine, 4 atmosphere furnace, 41 kiln body, 42 rotating bearing, 43 reaction section shell, 44 heating component, 45 feed end cover, 451 feed port, 46 discharge end cover, 461 discharge port, 462 air inlet, 47 drying section, 48 reaction section, 5 second ball mill, 6 second batching barrel, 7 third ball mill, 8 dehydrator, 9 molding machine, 10 calcining equipment, 11 cooling equipment. DETAILED DESCRIPTION
[0039] The following is a description of the implementation of the present invention by specific embodiments. People familiar with the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0040] Example 1, a method for preparing nano high aluminum material by using secondary aluminum ash fire method, combined with Figure 1As shown, the following steps are included:
[0041] Step (1) primary batching: 10 parts by weight of aluminum ash that has passed through a 100-mesh sieve are added to a first batching barrel 1, followed by 1 part of graphite, 0.1 part of boric acid, 0.5 part of calcium carbonate and 0.1 part of sodium silicate. After weighing, the mixture is added to a first ball mill 2 and dry-milled to an average particle size of 0.9 μm to obtain a mixed material. The mixed material is continuously and evenly added to a disc ball making machine 3. The mixed material moves with the disc ball making machine 3. During the process, a 3% sucrose solution is sprayed on the mixed material until the mixed material is rolled into a ball material with a diameter of 1.0 cm.
[0042] Step (2) primary pre-sintering: the ball material is sent to an atmosphere furnace 4 and calcined at 900°C in a nitrogen atmosphere for 3 hours to obtain a primary pre-sintered material; wherein the heating curve is: from room temperature to 300°C, the heating rate is 2°C / min; from 300°C to 900°C, the heating rate is 4°C / min;
[0043] Step (3) secondary batching: take the primary pre-sintered material by weight, crush it in the second ball mill 5, and then pass it through a 100-mesh sieve, take 10 parts of the sieved powder, add 5 parts of nano zinc oxide and 1 part of nano manganese oxide, 4 parts of aluminum sulfate, 3 parts of sodium aluminate and 0.02 parts of sorbitol, mix them, add them to 40 parts of water, add them to the second batching barrel 6, adjust the pH to 7 with citric acid, ball-mill in the third ball mill 7 until the average particle size is 0.9 μm, unload, centrifuge dehydrate in a dehydrator 8, and then form them in a molding machine 9 to obtain a green body with a water content of 6%;
[0044] Step (4) Calcination: The green body is sent to the calcination device 10 for calcination. The calcination process is as follows: room temperature-300°C at a rate of 4°C / min, 300°C-1000°C at a rate of 6°C / min, 1000°C-1500°C at a rate of 10°C / min, and heat preservation for 30 minutes. The green body is cooled in the cooling device 11 at a rate of 3°C / s to obtain the nano high-aluminum material.
[0045] like Figure 2As shown, the atmosphere furnace includes a rotating bearing 42, and a rolling cylindrical kiln body 41 mounted on the rotating bearing 42. The rolling cylindrical kiln body 41 ensures the fluidity of the ball material. Due to this structure, the diameter of the ball material is not easy to be too small. If it is too small, the fluidity will be poor and the kiln will be easily blocked. The two ends of the kiln body 41 are respectively connected to the feed end cover 45 and the discharge end cover 46 through the rotating bearing, which are used to close the kiln body 41 and make the kiln body 41 an anaerobic environment when working. The feed end cover 45 and the discharge end cover 46 are fixed structures and do not rotate with the kiln body 41. This is to ensure that the position of the feed port remains unchanged and the feeding is effective. The kiln body 41 is connected to the kiln body 41 through the rotating shaft The bearing connection can ensure the rotation of the kiln body 41, the feed end cover 45 is provided with a feed port 451, the discharge end cover 46 is provided with a discharge port 461 and an air inlet 462, and the air inlet 462 is used as a nitrogen inlet to ensure an anaerobic environment; the kiln body 41 is divided into a drying section 47 and a reaction section 48 according to the feeding and discharging direction, and the reaction section 48 is provided with a reaction section shell 43, and a heating component 44 is provided inside the reaction section shell 43. The drying section 47 is not provided with a heating component 44, but is dried by preheating the reaction section, and water vapor escapes from the feed port. The reaction section shell 43 mainly provides support for the heating component 44 and also has a heat preservation effect. The design of this structure meets the anaerobic calcination requirements of the one-time pre-burning of this scheme.
[0046] Example 2 is different from Example 1 in that, in step (1), 10 parts of aluminum ash are taken, and 2 parts of graphite, 0.2 parts of boric acid, 1 part of calcium carbonate and 0.5 parts of sodium silicate are added.
[0047] Example 3 is different from Example 1 in that, in step (1), dry grinding is performed to an average particle size of 1.0 μm.
[0048] Example 4 is different from Example 1 in that, in step (2), the calcination is performed at 900° C. for 4 h in a nitrogen atmosphere.
[0049] Example 5 is different from Example 1 in that, in step (3), 10 parts of the pre-burned material are taken, crushed and sieved through a 100-mesh sieve, 3 parts of nano zinc oxide and 2 parts of nano manganese oxide, 3 parts of aluminum sulfate, 4 parts of sodium aluminate and 0.02 parts of sorbitol are added, the mixture is added to 40 parts of water, the pH is adjusted to 8, and the mixture is ball-milled to an average particle size of 1.0 μm.
[0050] Comparative Example 1 is different from Example 1 in that direct sintering is performed, specifically:
[0051] Ingredients: Take 10 parts of aluminum ash 100 mesh sieved powder, add 5 parts of nano zinc oxide and 1 part of nano manganese oxide, 4 parts of aluminum sulfate, 3 parts of sodium aluminate and 0.02 parts of sorbitol, mix and add to 40 parts of water, adjust the pH to 7 with citric acid, ball mill to an average particle size of 0.9 μm, unload, centrifuge and dehydrate to obtain a green body with a water content of 6%;
[0052] Calcination: The green body is sent to the calcination equipment for calcination. The calcination process is room temperature-300℃ at a rate of 4℃ / min, 300℃-1000℃ at a rate of 6℃ / min, 1000℃-1500℃ at a rate of 10℃ / min, heat preservation for 130min, and cooling at a rate of 3℃ / s to obtain nano high aluminum material.
[0053] Comparative Example 2 is different from Example 1 in that no anaerobic treatment is performed during the primary pre-firing, that is, the atmosphere furnace has no feed end cover and discharge end cover.
[0054] Comparative Example 3 is different from Example 1 in that no graphite and boric acid are added in the first batching of step (1).
[0055] Comparative Example 4 is different from Example 1 in that 5 parts of graphite and 1 part of boric acid are added in step (1).
[0056] Comparative Example 5 is different from Example 1 in that no sucrose solution is used in the pelletizing process of step (2).
[0057] Comparative Example 6 is different from Example 1 in that, in step (2), the calcination is performed at 1100° C. in a nitrogen atmosphere for 4 h; and in step (3), the calcination is performed to an average particle size of 1.2 μm.
[0058] Comparative Example 7 is different from Example 1 in that, in step (4), the calcination process is to heat from room temperature to 300°C at a rate of 10°C / min, heat from 300°C to 1000°C at a rate of 6°C / min, heat from 1000°C to 1500°C at a rate of 10°C / min, and keep warm for 30 minutes. After cooling in a cooling device 11 at a rate of 5°C / s, a nano-high-aluminum material is obtained.
[0059] Comparative Example 8 is different from Example 1 in that in step (3), the moisture content of the green body is 3%.
[0060] Comparative Example 9 is different from Example 1 in that in step (3), the moisture content of the green body is 15%.
[0061] The main components of the selected aluminum ash are shown in Table 1:
[0062] Table 1
[0063]
[0064] The cross-sectional size of the mold for molding the green body of Examples 1-5 and Comparative Examples 1-9 was 20 mm × 15 mm, and the cut length during molding was 30 mm. The performance test results of the prepared finished products are shown in Table 1. The main test items include green body Cl content test, refractoriness test, and shrinkage test.
[0065] Green body Cl content detection: Undried green body is sampled and titrated to measure the green body Cl content;
[0066] Refractoriness test: reheat the prepared nano-alumina material to 1300℃ or above at five temperatures, with a heating rate of 20℃ / min, and observe whether there is any change or damage;
[0067] Shrinkage rate test: the volume change ratio of the prepared nano-high alumina material and the green body.
[0068] The results are shown in Table 2.
[0069] Table 2
[0070]
[0071] From the analysis of the results of Examples 1-5 and Comparative Examples 1-9, the present solution can obtain nano-high-aluminum materials with higher refractory strength and better shrinkage consistency, indicating that the large-scale production controllability is higher.
[0072] Halogens can harm the fire resistance of products. During the preparation process of Comparative Example 1, halogens were not completely removed, resulting in a high Cl content after firing, which led to performance degradation. At the same time, some aluminum nitride, fluoride, etc. in Comparative Example 1 were not completely removed through the process. These substances can have a toxic effect on the product. For example, nitrogen is produced during the high-temperature service process of aluminum nitride, forming microcracks, which in turn affects the fire resistance of the product; chloride salts react with oxygen in the furnace to generate chlorine. The chemical reaction between chlorine and refractory materials is one of the main reasons for the damage of spinel refractory bricks. Example 1 undergoes a pre-burning process to remove most of the aluminum nitride, and at the same time, fluoride is converted into a soluble salt, calcium fluorosilicate, through sodium silicate and calcium carbonate, and the halogen element is removed during the ball milling dehydration process.
[0073] In Comparative Example 2, the first pre-firing was not carried out in an anaerobic environment. The added graphite reacted with oxygen first to generate carbon dioxide, which could not decompose aluminum nitride. At the same time, graphite oxidation would also increase the system temperature, leading to grain growth, which would increase the average particle size of the first pre-firing material after ball milling, thereby reducing the total interface of the solid phase reaction during the second calcination, resulting in coarse grains, and ultimately leading to a decrease in refractory performance. The first pre-firing of Example 1 was carried out in an anaerobic environment. Graphite reacted with aluminum nitride to generate aluminum carbide. At the same time, boron atoms decomposed by boric acid and nitrogen-aluminum elements formed high-strength ceramic materials such as nitrogen-boron-aluminum. During the second calcination process, a small amount of dispersed high-strength ceramic materials such as nitrogen-boron-aluminum can become non-uniform nucleation points, hindering the expansion of cracks and enhancing the wear resistance and high temperature resistance of the product. Comparative Example 3 also has the problem of not completely decomposing aluminum nitride.
[0074] In comparative example 4, excessive graphite and boron are added. Excessive graphite will react to generate pores during the secondary calcination process, becoming the crack source of microcracks. Excessive boric acid reacts with nitrogen and aluminum to generate excessive high-strength ceramic materials such as nitrogen, boron, and aluminum, which destroys the crystal phase continuity of the nano-high-aluminum material and leads to a decrease in overall performance. At the same time, there is also the problem that excessive graphite increases the temperature of the secondary calcination system, resulting in abnormal growth of local grains, which also reduces the refractory strength of the nano-high-aluminum material.
[0075] In comparative example 5, no sucrose solution was used, resulting in lower strength of the ball material, which was easily broken during the primary pre-firing process, causing the material in the kiln body to compact in the reaction section, affecting the stability of the material flow in the kiln body. The unstable material flow will cause differences in the calcination process for each ball material, ultimately resulting in a greater degree of randomness in the primary pre-firing effect, which poses a hidden danger to the stability of product performance.
[0076] The performance of Comparative Examples 6 and 7 is lower than that of Example 1 because the calcination process has the problem of too high temperature or too long holding time resulting in excessively coarse grains, especially in Comparative Example 7, where the too fast cooling rate causes inconsistent shrinkage of the phases, resulting in the presence of surface microcracks.
[0077] The green body of Comparative Example 8 is too dry, and cracks are easily formed on the surface itself; the green body of Comparative Example 9 is too wet, and the internal moisture cannot escape in time during the secondary calcination, resulting in cracks during the heating process.
Claims
1. A method for preparing nano high-aluminum material using a secondary aluminum ash fire method, characterized in that: The following steps are involved: Step (1) primary batching: taking 10 parts by weight of aluminum ash passed through a 100-mesh sieve, adding 1-2 parts of graphite, 0.1-0.2 parts of boric acid, 0.5-1 parts of calcium carbonate and 0.1-1 parts of sodium silicate, dry-grinding to an average particle size of 0.8-1.0 μm to obtain a mixed material, and pelletizing the mixed material to obtain a ball material; Step (2) primary pre-calcination: the ball material is sent to 800-1000°C and calcined in anoxic conditions for 2-4 hours to obtain a primary pre-calcined material; Step (3) secondary batching: taking 10 parts of the primary pre-sintered material by weight, crushing it and passing it through a 100-mesh sieve, adding 4-6 parts of nano metal oxide particles, 3-5 parts of aluminum sulfate, 3-4 parts of sodium aluminate and 0.01-0.03 parts of a dispersant, mixing and adding to 30-50 parts of water, adjusting the pH to 6-8 with a pH regulator, ball milling to an average particle size of 0.8-1.0 μm, unloading, dehydrating and molding to obtain a green body; Step (4) calcining: sending the green body into a calcining device for calcining, and obtaining a nano high-aluminum material after cooling; In step (1), the mixing ball making process is as follows: continuously and evenly adding the mixing material into the disc ball making machine, the mixing material moves with the disc ball making machine, and during the process, a sucrose solution with a concentration of 1%-5% is sprayed on the mixing material until the mixing material is rolled into a ball material with a diameter of 0.8-1.5 cm; In step (2), the temperature rise process of the anaerobic calcination is: room temperature to 300°C, the heating rate is 1-3°C / min; 300°C-final temperature, the heating rate is 3-5°C / min; In step (3), the moisture content of the green body is 5-8%; In step (4), the calcination process is as follows: heating from room temperature to 300°C at a rate of 3-5°C / min, heating from 300°C to 1000°C at a rate of 5-8°C / min, heating from 1000°C to final temperature at a rate of 8-15°C / min, and keeping warm for 10-30 minutes; the final temperature is 1250-1550°C; and the cooling rate is 0.5-5°C / s.
2. The method for preparing nano high-aluminum material by secondary aluminum ash pyrolysis as claimed in claim 1, characterized in that: In step (2), the anaerobic calcination is calcination under a nitrogen atmosphere.
3. The method for preparing nano high-aluminum material by secondary aluminum ash pyrolysis as claimed in claim 1, characterized in that: In step (3), the nano metal oxide particles are one or more of nano magnesium oxide, nano zinc oxide, nano manganese oxide, and nano iron oxide; the pH regulator is citric acid; the dispersant is sorbitol or calcium gluconate; and in step (3), the dehydration method is centrifugal dehydration.
